1998
DOI: 10.1017/s0033291797006387
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between negative emotions and acute subjective and objective symptoms of childhood asthma

Abstract: Negative emotions affect subjective, rather than objective symptoms of childhood asthma. It was suggested that children in a negative emotional state, uncertain about the condition of their airways, are inclined to interpret exercise-related general sensations (fatigue, heart pounding, sighing) in line with expectations as symptoms of airways obstruction. Consequently, they may report relatively high breathlessness, irrespective of actual objective symptoms of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 41 publications
5
35
0
Order By: Relevance
“…However, asthma-PD patients reported greater use of short-acting β 2 -agonist medication. In addition, asthma-PD patients reported greater emotional disturbance connected with asthma, and they had a high rate of comorbid depression, which may contribute to magnification of asthma symptoms (21,34).…”
Section: Discussionmentioning
confidence: 99%
“…However, asthma-PD patients reported greater use of short-acting β 2 -agonist medication. In addition, asthma-PD patients reported greater emotional disturbance connected with asthma, and they had a high rate of comorbid depression, which may contribute to magnification of asthma symptoms (21,34).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that emotionally engaged physicians communicate more effectively with patients thereby decreasing patient anxiety and improving patient coping, leading to greater therapeutic efficacy and an overall better outcome. (Beck et al, 2002, Rietveld andPrins, 1998). On the other hand, lack of empathy increases patient dissatisfaction and the risk of malpractice suits.…”
Section: The Power Of Empathymentioning
confidence: 99%
“…Negative emotions have been linked to decreased involvement in exercise along with increased symptom reporting among school aged children with asthma (Meyer, Kroner-Herwig & Sporkel, 1990;Panditi & Silverman, 2003;Pianosi & Davis, 2004;Rietveld & Prins, 1998).The more negative the child perceives the situation (such as exercise) the higher the likelihood they will report subjective symptoms such as increased breathlessness and fatigue (Panditi & Silverman; Rietveld & Prins). When presented with an unfamiliar task or situation such as participating in an exercise event, children with asthma may perceive the situation as anxiety provoking, thus leading to increased sensation of shortness of breath.…”
Section: Negative Emotions Influence On Exercisementioning
confidence: 99%
“…As the available research has shown, the majority of the literature focuses on perceptions of physical functioning abilities, physical self-concept, misperceptions of exercise, emotions affecting exercise, and attitudes towards exercise (Kiviniemi et al, 2007;Meyer et al, 1990;Panditi & Silverman, 2003;Pianosi & Davis, 2004;Rietveld & Prins, 1998;Welsh et al, 2005;Wirrrell et al, 2006). However, very few articles were identified specifically focusing on perception of exercise from the perspective of the school aged child with asthma.…”
Section: Chapter Summarymentioning
confidence: 99%